CRAFTING CORPORATE SOCIAL RESPONSIBILITY (CSR): A CASE STUDY OF CSR STRATEGIZING AND INSTITUTIONALIZATION - Krikorian, Frederic (2009)
This dissertation aims to fill a gap in CSR research by adopting a constructivist perspective to investigate how CSR practitioners craft strategies and how this contributes to the institutionalization of CSR in general, and of the ‘business case for CSR’ in particular. It does so by relying on the strategy-as-practice approach and the notions of institutional entrepreneurship and institutional work. This dissertation is based on a single-case study of two CSR practitioners who implemented a CSR strategy in a UK energy firm.